STRATEGY TO INCREASE SATISFACTION IN SHAPING STUDENT BEHAIOR IN STIKES HARAPAN BANGSA PURWOKERTO - Yuliarti, Lusi (-)
The purpose of this research is to know the influence of physical evidence, location,and  image  on satisfaction on the loyality  of  college student  in the STIKES Harapan Bangsa Purwokerto. This study is a survey. The data is primary data taken by sampling method, as many as 125 respondents. Data analyzed with validity and reliability test, partial test ( t test ), simultaneously test ( F test ), R-square and path analysis. T test result shows that : physical evidenc is significant positive  effect on satisfaction, location is insignificant positive effect on satisfaction,  image    is insignificant positive effect on satisfaction, physical evidenc is significant positive  effect on loyality, location is insignificant positive effect on loyality,  image    is insignificant negatie  effect on loyality, satisfaction is significant positive effect on loyality. F test result shows that simultaneously physical evidence, location,and  image  has significant positive effect on the performance.  R-square test result shows that  84,7  % variation of loyality can be explained by physical evidence, location,  image,and satisfaction  the remaining 15,3% is explained by other factors out of the model. The path analysis show : the direct effect of  physical evidence on loyality variables is smaller  than the indirect effect of physical evidence on loyality by mediating satisfaction. Based on a total leverage to improve loyality  will be more effective if through increased discipline by mediating  satisfaction  Keywords : physical evidence, location, image, satisfaction, loyality